Integrating Indigenous Knowledge into Chadian Primary Science: A Phenomenological Inquiry with Teachers - Mahamat Adoum; Abderaman Koulamallah; Aïcha Abdelkerim (International Journal of Education and Learning Studies, 2025)
This qualitative phenomenological study investigates the perspectives of primary school teachers in Chad on integrating Indigenous Knowledge (IK) into the science curriculum. Based on in-depth interviews with 25 teachers, the analysis revealed three key themes. First, while teachers universally acknowledged IK's pedagogical value for enhancing student engagement and comprehension, their own understanding of IK remained superficial and anecdotal. Second, a significant professional development gap was evident, with teachers reporting no training in ethnoscience or culturally responsive methods, leading to low confidence in integration. Third, formidable systemic barriers were identified, including a rigid, overloaded national curriculum, high-stakes examinations, and severe resource constraints, which collectively stifle pedagogical innovation. The findings reveal a critical misalignment between teachers' supportive aspirations for IK and the systemic realities that constrain implementation. The study concludes that sustainable integration requires a multi-pronged approach involving curriculum reform to allow local contextualization, comprehensive teacher professional development in culturally sustaining pedagogies, and the provision of context-specific teaching resources. By centering teacher voices, this research contributes directly to policy discussions on educational reform in Chad and offers critical insights for the broader discourse on decolonizing science education in Africa.